Malaysian adolescents’ moral awareness and cultural conformity: some implications for today’s educational management - Abd Hamid, Siti Rafiah; Nik Abdul Rahman, Nik Suryani; Ismail, Khamsiah; Rais, Haniza (IIUM Press, International Islamic University Malaysia, 2018)
It has been reported in printed and electronic media that moral decadency among Malaysian adolescents is on the rise. 2 Such decadency is attributed by a host of “nature versus nurture” debatable factors. This study aims at describing the moral awareness and cultural conformity of Malaysian adolescents. A questionnaire was administered on 200 respondents. Preliminary findings indicated that the respondents’ conformed positively to their cultural expectations (M= 3.92; SD= .92) and have positive moral awareness is (M = 4.40; SD = .85). These findings were perceived instrumental to the current classroom managements, school counseling services and choice of parenting styles in Malaysia.